Conflict-related and sexual trauma in treatment-seeking Arabic-speaking men: a cross-sectional studyResearch in context - Max Vöhringer; Freya Specht; Christine Knaevelsrud; Birgit Wagner; Maria Böttche; Yuriy Nesterko (EClinicalMedicine)
Summary: Background: Sexual trauma in the context of conflict and displacement is considered one of the most serious and stigmatising forms of human rights violations. Although it has occurred throughout history, research data on this topic is scarce, especially regarding male survivors and Arabic-speaking countries. In the present study, we examined sexual and conflict-related trauma prevalence rates and those of other trauma types, as well as associations with sociodemographic and psychological characteristics among men from Arabic-speaking countries in the Middle East and North Africa (MENA) region seeking treatment via the internet. Methods: In a cross-sectional and exploratory study design, prevalence rates of different trauma types were examined in a sample of treatment-seeking Arabic-speaking men. Sociodemographic characteristics, psychological symptom scores, disclosure rates, and trauma-related cognitive alterations were compared between participants reporting sexual trauma only (STo), conflict-related trauma only (CRTo), both trauma types (ST + CRT), and other trauma types (Non-ST/CRT). For the primary outcomes (psychological symptoms and trauma exposure) the group differences were analysed using an ANOVA and post-hoc pairwise group comparisons. The data collection took place between February 2021 and March 2023. Findings: In total, 3903 men were initially screened. Of these, 2138 men indicated having experienced at least one traumatic event from a list of 23 types of events (man-made and non-man-made trauma) and were included in the study (age median: 25, age interquartile range: 10). 22% (n = 471) of participants were categorised into the STo group, 5.9% (n = 127) into the ST + CRT group, 18.6% (n = 397) into the CRTo group, and 53.5% into the Non-ST/CRT group (n = 1143). The ST + CRT group scored higher on measures of depression and posttraumatic stress disorder (PTSD) compared to all other groups; significant differences between the groups were found on both these primary outcomes (depression: F(df) = 3.65 (3, 503.33), p < 0.05; PTSD: F(df) = 5.71 (3, 507.57), p < 0.01). However, these outcomes did not differ significantly between the ST + CRT group and the STo group. Furthermore, the STo and ST + CRT groups showed the highest scores for trauma appraisal and posttraumatic maladaptive beliefs, with no significant differences between them. Notably, the STo group scored significantly lower on the measure of disclosure to others than both the CRTo group (adjusted mean difference [aMD] = −1.14, 95% CI [−1.56, −0.71], p < 0.001) and the Non-ST/CRT group (aMD = −0.90, 95% CI [−0.58, −1.22], p < 0.001). Additionally, the STo group scored greater trauma-related guilt compared to the CRTo (aMD = 0.45, 95% CI [0.29, 0.61], p < 0.001) and the Non-ST/CRT groups (aMD = 0.21, 95% CI [0.33, 0.09], p < 0.001). Interpretation: The results of this exploratory study reveal that a substantial proportion of Arabic-speaking treatment seeking men from different countries in the MENA region reported experiences of sexual and conflict-related trauma, which were associated with high psychological symptom scores. The parallels with survivors of sexual violence occurring in other contexts emphasise the need for sensitivity of researchers and practitioners when assessing sexual violence in male patients. Clinicians should furthermore bear in mind the cognitive alterations and significant barriers to disclosure, which reflect societal taboos and stigma, when working with survivors. Funding: The project was funded by Misereor e.V.